Generation Z Women's Attitudes Towards Women's Dual Role Decisions - Nurbaiah, Salwa; Ninin, Retno Hanggarani; Hanami, Yuliana (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2025)
Mature this , increasingly Lots woman educated and open opportunity for they participate in various sector . With thus , the more Lots woman decide For play a role double . Although role double can done woman or man , will but term the tend associated For women who have Marry as well as operate activities in the realm domestic and public . However , the decision For play a role bring up challenge separate research​ This important For done Because undergo role double is not easy things​ for women , especially when must face difficulty in balance between the main answer work and family . Imbalance This can cause various problem such as : conflict , tension psychological , burnout , which ultimately influence flexibility work . Research This aim For explore attitude Gen Z women towards decision role double woman . Writer use approach qualitative descriptive with technique convenience sampling . Researchers This involving five participants woman from Generation Z aged 20-26 years who have understanding about role double . Research results show generally woman Generation Z supports role double woman with motivation main in the form of achievement independence financial , fulfillment actualization self , and improvement mark yourself in society . However , they​ realize existence challenges , such as balance role , pressure psychological , and potential conflict between work and life . Factors that influence formation attitude This covering awareness individual , orientation goals , and influence from family , friends and social media . With That's how Gen Z women see it role double as choices that require strategy, such as management effective time and strong support​​ especially from partner For reach balance career and life personal .